The Impact of Audit Committee’s Financial Expertise and Status on Accrual Earnings Management - Rindi Fitria Dewi; Aria Farah Mita (Institute of Research and Community Outreach - Petra Christian University, 2019)
This research aims to study the impact of the audit committee’s financial expertise and status on accrual earnings management. This study focuses on the status of audit committee relatives to the board of director. Status is measured by their current or previous employment in the BEI listed companies, the intra-industry of BEI listed companies, the financial companies of BEI listed or in the financial institutions; in the government; and a degree from elite educational institutions. A sample of non-financial companies is used with a period observation of 2015-2016 and a total observation of 580 firm-years. The result of this research indicates that the audit committee financial expertise has a significant effect on accrual earnings management. The audit committee status has no significant effect on accrual earnings management.